Developing a Model of Citizenship Education in Smart Cities - Gholami, Zahra; Reshadatjoo, Hamideh; Zamani Moghadam, Afsaneh (Assessment and Practice in Educational Sciences, 2024)
The present study was conducted with the aim of developing a model of citizenship education in smart cities. From the perspective of its purpose, this study is a fundamental–applied research. In terms of data, it used a mixed-methods design, and regarding its implementation method, it followed a grounded theory approach (based on interviews with experts). In the quantitative phase, survey models were employed to collect research data. The qualitative population consisted of academic experts and senior managers of the municipalities of Tehran, Tabriz, and Mashhad. A purposive non-random sampling method was used, and according to the principle of theoretical saturation, 20 participants were selected as the qualitative sample. The quantitative population included 68,000 managers and employees of the Tehran Municipality. To determine the sample size for the quantitative phase, Cochran’s formula was applied, resulting in a sample of 380 managers and employees of Tehran Municipality. A multistage cluster sampling technique was used for sample selection in the quantitative phase. In the qualitative section, semi-structured in-depth interviews were conducted, and in the quantitative section, a researcher-developed questionnaire was utilized. To ensure the validity of the instruments in the qualitative phase and to verify the accuracy of findings from the researcher’s perspective, the opinions of university professors and domain specialists were employed. The reliability of the interviews was established using the test–retest method and inter-subject agreement. For determining the validity of the questionnaire, face validity, content validity, and construct validity were examined. Reliability was assessed through Cronbach’s alpha and composite reliability, both of which were confirmed. Data analysis in the qualitative phase was performed using theoretical coding. In the quantitative phase, based on the research questions, descriptive statistics (mean, standard deviation, skewness, and kurtosis) were analyzed using SPSS version 21, while inferential statistics—including Pearson correlation and confirmatory factor analysis—were performed using SPSS-V21, SMART PLS-V2, and LISREL-V8 software packages. The results of the study indicated that citizenship education in a smart city encompasses dimensions such as educational objectives, content, and evaluation. Moreover, the factors influencing citizenship education in smart cities include dimensions of support and information technology, while the outcomes of citizenship education were identified as increased literacy and civic participation. In conclusion, a conceptual model was developed based on the grounded theory approach, which demonstrated acceptable validity.